Electrophoretic detection of salivary alpha-amylase activity - Rahim, Z.H.; Yaacob, H.B. (1992)
Fresh samples of human whole saliva containing approximately 20-40 micrograms protein were analyzed using SDS-polyacrylamide slab gel electrophoresis systems. More than 20 protein bands were revealed by Coomassie Brilliant Blue R 250 staining. Some of the protein bands were shown to be glycoprotein-positive with PAS (periodic acid-Schiff) reagent. The protein bands with alpha-Amylase activity appeared within a molecular weight range of 120,000-180,000, which is 2 to 2.8 times higher than the normal molecular weight reported for alpha-Amylase from parotid saliva, and showed positive staining with PAS reagent. These results show that the alpha-Amylase in whole saliva appears to exist in a macromolecular form which is not dissociated in the presence of sodium dodecyl sulfate (SDS).